Adolescents' adherence to Centers for Disease Control and Prevention guidelines during the COVID‐19 pandemic. (21st April 2022) - Clough, Isabelle M.; Drozdova, Anna D.; Cavanagh, Caitlin; Gile Thomas, April
Abstract: Background: The outbreak of the coronavirus (COVID‐19) pandemic in the United States resulted in safety guidelines from the Centers for Disease Control and Prevention (CDC) intended to curb the spread of the virus. Adolescents are potentially at risk for disregarding these guidelines due to their reduced psychosocial maturity compared with adults. The current study examined the relationship between adolescents' psychosocial maturity, perceived importance of the CDC guidelines and adherence to the CDC guidelines within some of the highest risk groups for contracting COVID‐19 in a county particularly impacted by the pandemic (i.e., Hispanic and low‐SES youth in El Paso, Texas). Methods: Participants completed a phone interview with a research assistant regarding their thoughts and behaviours in the initial months of the COVID‐19 pandemic. Adolescents ( N  = 68) were 15.38 years old on average ( SD  = 1.05, range  = 13, 17), predominantly male (60.3%) and nearly exclusively Hispanic/Latino (94.1%). Results: Results indicated that although more psychosocially mature adolescents reported greater adherence to the CDC guidelines than less psychosocially mature adolescents, the association between psychosocial maturity and adherence was fully mediated by how important adolescents felt it was to follow the guidelines. Specifically, greater perceived importance was associated with greater adherence to the guidelines. Conclusions: The current study found that more psychosocially mature adolescents adhere to CDC's safety guidelines better than less psychosocially mature adolescents because they are more likely to view the guidelines as important. Information that attempts to increase adolescent adherence to the guidelines should therefore emphasize not only that following the guidelines is important, but why following the guidelines is so important. Less psychosocially mature adolescents may benefit most from interventions efforts and targeted messages regarding the importance of following the CDC's guidelines, as more psychosocially mature adolescents already recognize this importance.